Spectrophotometric Determination of Chromium in Water, and Pharmaceutical Samples Using 1-Naphthol - K. Suvardhan; S. Ramanaiah; K. Suresh Kumar; D. Rekha; Umayur Bhagan; G. R. K. Naidu; G. Krishnamurthy Naidu; B. S. Sastry; P. Chiranjeevi (E-Journal of Chemistry)
Facile and sensitive spectrophotometric methods for the determination of trace and ultra trace amounts of chromium (VI) are described. 4-aminoantipyrine (APP) reacts with 1-naphthol (NPL) in presence of oxidising agent potassium dichromate in acidic medium to produce red coloured product having λmax of 485 nm. The molar absorptivity and Sandell's sensitivity were 2.07x104 l mol-1 cm-1 and 0.00240 μg/cm2 respectively. The colour is stable for more than 6 h. The system obeys Beer's law in the range, 2-18 μg for determination of chromium (VI). The detection limits of chromium (VI) is 0.048 μg mL-1. The method is highly reproducible and has been applied to the analysis of chromium in synthetic, natural water samples and pharmaceutical preparations and the results compared favourably with the reported method.